In the outskirts of civilization: The other city according to the hygienists of the Lima of the nineteen hundred - Ramón, Gabriel (1998)
The word suburb comes from the Hispano-Arabic of the twelfth century and defines the neighborhood located in the confines of a population. In its demonym (outskirts) it acquires an extremely pejorative connotation. Civilization is both earlier (because of its roots) and later, because in its full acceptance it began to be used only in the 18th century, alluding both to the action and effect of civilizing and to the "social status of a people". Both terms share a subtle ambivalence, being both political and spatial. Their correspondence makes it essential to consider one to understand the other and in response to this, it is intended to characterize the Lima civilization of the nine hundred from its action and reaction to the occupants of the suburb. The limits will be taken as an essential part of the definition.